Comparing occupation based intervention with traditional therapy for patients with de quervain's disease - Meier, Jaqueline (My University, 2019)
Introduction: There is a need for occupational therapists working in hand rehabilitation practices in South Africa to realign with the profession’s philosophy by providing occupation based interventions (OBI). A growing body of evidence points towards OBI for producing favourable outcomes in physical rehabilitation practices, however no studies have reported the outcomes of this method with de Quervain’s disease. This research was conducted to develop and compare the outcomes of an OBI programme to a traditional immobilisation protocol for de Quervain’s disease. Methodology: A quantitative- longitudinal pre-test post-test research intervention design was used in this study. Total population sampling was used with 54 patients diagnosed with de Quervain’s disease at Helen Joseph Hospital, with 27 patients conveniently recruited into each treatment group in the order they were referred. A demographics questionnaire was developed for the study and the outcome measures included the Finkelstein Test, Visual Analogue Scale, Disabilities of the Arm, Shoulder and Hand questionnaire (DASH), and the Canadian Occupational Performance Measure (COPM). Data were analysed using Statistica 13.2, and descriptive, parametric and non-parametric statistical tests were used to compare the outcomes within and between the two treatment groups. Results: No significant differences in outcomes were shown between the two treatment groups at the end of a six-week intervention period. Significant improvements in scores were however shown for the OBI group compared to the traditional group for the DASH work (p=0.010) and COPM performance (p=0.014) and satisfaction (p=0.041) assessments three weeks into the intervention. Conclusion: Both the OBI and traditional groups produce favourable outcomes for de Quervain’s disease at the end of a six-week intervention period, however the process to achieve these outcomes is more satisfying for patients who receive OBI
A Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Occupational Therapy Johannesburg June 2019